Curcumin Regulates the r(CGG)exp RNA Hairpin Structure and Ameliorate Defects in Fragile X-Associated Tremor Ataxia Syndrome - Verma, Arun Kumar; Khan, Eshan; Mishra, Subodh Kumar; Mishra, Amit; Charlet-Berguerand, Nicolas; Kumar, Amit (Frontiers in Neuroscience, 2020)
Fragile X-associated tremor ataxia syndrome is an untreatable neurological and neuromuscular disorder caused by unstable expansion of 55 to 200 CGG nucleotide repeats in 5′ UTR of Fragile X mental retardation 1 (FMR1) gene. The expansion of CGG repeats in the FMR1 mRNA elicits neuronal cell toxicity through two main pathogenic mechanisms. First, mRNA with CGG expanded repeats sequester specific RNA regulatory proteins resulting in splicing alterations and formation of ribonuclear inclusions. Second, repeat-associated non-canonical translation (RANT) of the CGG expansion produces a toxic homopolymeric protein, FMRpolyG. Very few small molecules are known to modulate these pathogenic events, limiting the therapeutic possibilities for FXTAS. Here, we found that a naturally available biologically active small molecule, Curcumin, selectively binds to CGG RNA repeats. Interestingly, Curcumin improves FXTAS associated alternative splicing defects and decreases the production and accumulation of FMRpolyG protein inclusion. Furthermore, Curcumin decreases cell cytotoxicity promptly by expression of CGG RNA in FXTAS cell models. In conclusion, our data suggest that small molecules like Curcumin and its derivatives may be explored as a potential therapeutic strategy against the debilitating repeats associated neurodegenerative disorders.